Diagnostic accuracy and clinical application of faecal calprotectin in adult patients presenting with gastrointestinal symptoms in primary care. (September 2013) - Pavlidis, Polychronis; Chedgy, Fergus JQ; Tibble, Jeremy A
Abstract: Objective. Assessment of faecal calprotectin (fCal) test performance in primary care within an irritable bowel syndrome (IBS) diagnostic pathway. Methods. Study based on consecutively collected fCal data from 962 patients, aged 18–45, presenting to their general practitioner (GP) with persistent gastrointestinal symptoms. Results. Six hundred and eighty six (71%) patients had a negative (<50 μg/g) and 276 (29%) had a positive fCal. 28% (77/276) of the patients testing positive and 3% (17/686) of those testing negative had an organic diagnosis. At 50 μg/g the sensitivity of the test for organic disease was 82%, (95% confidence interval [CI] 73–89) and the specificity was 77% (95% CI 74–80), with negative predictive value (NPV) and positive predictive value (PPV) of 98% and 28%, respectively. A cut-off increase to 150 μg/g reduces the NPV by 1% whilst increasing the PPV to 71%. This would reduce colonoscopy and flexible sigmoidoscopy bookings by 10% at the cost of four missed cases of inflammatory bowel disease. Conclusions. This study provides the first evidence on the use of fCal testing in primary care. The low prevalence of organic disease in this setting has a significant impact on test performance. This suggests a need for change in cut-off value, to improve PPV whilst accepting a reduction in test sensitivity, if it is to be used as part of the pathway for management of patients with suspected IBS.